Sustainability Analysis of Yard Management in Ecological Aspects - Arini, Nadia; Hidayat, Kliwon; Cahyono, Edi Dwi (Postgraduate School of Universitas Brawijaya, 2024)
The yard is one land use formed through human interaction with the environment. This research uses human ecology theory, which discusses the reciprocal relationship between the Trucuk village community (social system) and the yard (biophysical system). This study aims to describe the yard's condition and identify the meaning, function, and factors influencing yard management. This study used a combined quantitative and qualitative approach (mixed methods). The design used for the quantitative approach is a survey, and a case study for the qualitative approach. The sampling technique in this study was cluster sampling. Most communities in Trucuk village have a yard with an area of <120 m2. 75% of the communities manage their yards, while 25% neglect them. The meaning of the yard in the Trucuk Village Community is to refurbish the houses and food barns, increase family income, empty land use, plant hobbies, and act as an asset. The functions of the yard include gene resource conservation and socio-economic and aesthetic functions. This research can be used as a reference for empowerment activities or village community development. Keywords: food barns, human ecology, socio-economic, yard